PEMEROLEHAN BAHASA PERTAMA ANAK USIA 10 BULAN (studi kasus pada anak laki-laki bernama Muhamad Hafiz Firdaus) - Ade Eka Anggraini (Jurnal Membaca Bahasa dan Sastra Indonesia, 2016)
Language acquisition is a process of human language development. Typically the first language acquisition is associated with the development of children’s language when acquiring a second language, relying on the development of adult language (Language Acquisition). The focus of this study, researchers only limit on the development of the field of phonology in language acquisition Prespeech form. This research method is descriptive qualitative method. Based on the results, it can be concluded that Hafiz had been able to utter the words that still dikegorikan chatter, mixed with blowing vocal sound that appears when imitating, the words begin to differ. So, in child language acquisition will learn the words or movements he needs to express something he wanted or did not want.